Growth in atopic eczema. Issue 5 (May 1993) - Massarano, A A; Hollis, S; Devlin, J; David, T J
Abstract : Growth was studied in 68 children aged 2-12 years with atopic eczema. Height SD scores were significantly correlated with the surface area of skin affected by eczema. The mean height of 41 patients with less than 50% of their skin surface affected (group I) was normal (mean SD score -0.11). The 27 children with more than 50% of their skin affected (group II) were significantly shorter (SD score -0.83) and were also short allowing for their parental target height. The predicted heights were also normal in group I but were lower than expected in group II. Regression analysis suggested that height was most dependent on parental height. The extent of the disease had a significant additional effect, whereas dietary treatment and treatment with topical steroids had only marginal additional effects. The growth of children with eczema affecting less than 50% of the skin surface area appears to be normal, and impaired growth is confined to those with more extensive disease.